f(x) = tan2(x) + (√3 - 1)[tan(x)] - √3 = 0
tan2(x) + √3[tan(x)] - tan(x) - √3 = 0
Factor into
[-1 + tan(x)]*[√3 + tan(x)] = 0
which means
[-1 + tan(x)] = 0 and/or [√3 + tan(x)] = 0
Then
tan(x) = 1
tan-1(1) = pi/4 radians
For the other equation
[√3 + tan(x)] = 0
tan(x) = -√3
tan-1(-√3) = -pi/3
so that
x = pi/4 or -pi/3 in the interval [0, 2pi]
Answer:
3
Step-by-step explanation:
9/4÷3/4
9/4 ×4/3
which would equal 3
Step-by-step explanation:
6x - 15 = 75, 6x = 90, x = 15.
2(2x - 1) = 46, 2x - 1 = 23, x = 12.
x + (x - 10) = 26, 2x = 36, x = 18.
5x - 3x = 10, 2x = 10, x = 5.
Hence the equations
in increasing order of x-values are:
5x - 3x = 10,
2(2x - 1) = 46,
6x - 15 = 75, and
x + (x - 10) = 26.
Answer:
Subtraction property of equality.